Collaborative learning methods and multimedia tools for the education and training of instructors: The case of FIFA referee technical instructors. Issue 5 (29th March 2019) - Armenteros, Manuel; Benítez, Anto J.; Fernández, Marta; De la Vega, Ricardo; Sillero-Quintana, Manuel; Sánchez Cid, Manuel
Abstract : Purpose: The purpose of this paper is to analyze the new collaborative learning methods and tools used by elite FIFA referee technical instructors, referees and assistant referees to master the Laws of the Game. These tools allow instructors to learn through practical exercises off the field of play, while they carry out activities in a participative context in which they can share and improve their knowledge regarding the Laws of the Game and consequently the interpretations and the considerations soccer referees throughout the world use to make decisions on the field of play. Design/methodology/approach: In this work, we assess a collaborative learning experience that took place during the annual FIFA FUTURO III courses that FIFA provided to FIFA referee technical instructors from its six confederations between 2013 and 2015, where 48 referee technical instructors selected from 211 national associations participated. These instructors constitute the elite of FIFA's professional training and development chain. They teach other referee technical instructors who will then instruct international referees and assistant referees all over the world with the aim of achieving uniformity when applying the Laws of the Game. Findings: The course participants showed a high degree of satisfaction with respect to these materials and methods, especially regarding the possibilities they offer for organizing group discussions and for "learning by doing, " and a lack of skills in ICT management has been detected for some participants, who have shown a willingness and interest to improve their skills in this field. Research limitations/implications: The training and education of soccer referees is one of the most heterogeneous training processes in the world. This complex task is even more difficult because of the growing demand for video technology in referee decision making where successful teamwork requires a high level of communication and agreement among its members. Practical implications: With 211 associations, FIFA is one of the largest organizations in the world. In international competitions such as the FIFA World Cup, the referees' decisions are analyzed by media, thousands of fans and millions of viewers. Preparing new professionals for match analysis, interpretation of Laws of the Game and working in a team is a priority for FIFA and the world of soccer. Originality/value: It is the first time that collaborative learning methods are used with interactive multimedia tools that facilitate collaborative work in the training environment of soccer referee instructors, international soccer referees and assistant referees. This paper establishes a basis and a reference for future research on the effectiveness of the new collaborative technologies used by FIFA for the training of international referees and assistant referees in general.